2006
DOI: 10.1016/j.febslet.2006.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Haemozoin (β‐haematin) biomineralization occurs by self‐assembly near the lipid/water interface

Abstract: Several blood-feeding organisms, including the malaria parasite detoxify haem released from host haemoglobin by conversion to the insoluble crystalline ferriprotoporphyrin IX dimer known as haemozoin. To date the mechanism of haemozoin formation has remained unknown, although lipids or proteins have been suggested to catalyse its formation. We have found that beta-haematin (synthetic haemozoin) forms rapidly under physiologically realistic conditions near octanol/water, pentanol/water and lipid/water interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
190
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(204 citation statements)
references
References 32 publications
14
190
0
Order By: Relevance
“…This means that the metal complex probably accumulates near water-lipid interface regions within the digestive vacuole of the parasite, rather than deeply inside the aqueous regions where CQ concentrates. This observation, together with the idea that lipids catalyze heme aggregation within plasmodium food vacuoles [47,48] and with the findings of Egan et al [36] that β-hematin spontaneously forms by rapid self-assembly near octanol-water or lipid-water interfaces can explain the enhanced antimalarial activity of complex 1 both in vitro and in vivo, when compared with CQ. Furthermore, the fact that the complex is active against CQ-resistant strains of P. falciparum may also be related to its greater lipophilicity, in line with previous reports indicating a lowered ability of the mutated transmembrane transporter PfCRT to promote the efflux of highly lipophilic drugs [40,51].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…This means that the metal complex probably accumulates near water-lipid interface regions within the digestive vacuole of the parasite, rather than deeply inside the aqueous regions where CQ concentrates. This observation, together with the idea that lipids catalyze heme aggregation within plasmodium food vacuoles [47,48] and with the findings of Egan et al [36] that β-hematin spontaneously forms by rapid self-assembly near octanol-water or lipid-water interfaces can explain the enhanced antimalarial activity of complex 1 both in vitro and in vivo, when compared with CQ. Furthermore, the fact that the complex is active against CQ-resistant strains of P. falciparum may also be related to its greater lipophilicity, in line with previous reports indicating a lowered ability of the mutated transmembrane transporter PfCRT to promote the efflux of highly lipophilic drugs [40,51].…”
Section: Discussionmentioning
confidence: 57%
“…This is important in connection with the proposal that lipids catalyze heme aggregation, probably by increasing heme solubility in acidic environments [47]; neutral lipids that catalyze the formation of hemozoin in vitro have been shown to form lipid bodies associated with plasmodium food vacuoles [48]. Egan et al [36] recently demonstrated that under acidic physiologically realistic conditions β-hematin spontaneously forms by rapid selfassembly near octanol-water, pentanol-water, or lipid-water interfaces. Our partition data (Fig.…”
Section: Partition Coefficient Measurements As a Function Of Phmentioning
confidence: 99%
See 2 more Smart Citations
“…On the premise that hemozoin nucleation is induced via a surface layer of lipid glycerol groups that expose OH, CH 2 , and oxygen lonepairs, nucleation was predicted to occur via the {100} face, which exposes CO 2 H and C─H groups (5). Precipitation of micron-sized crystals of β-hematin from a myristoyl-glycerol solution/water interface was reported by Egan et al (6). The orientation of such crystals at the water surface was identified by grazing incidence X-ray diffraction, revealing crystals floating on their {100} faces, but not the presence of lipid layers (7).…”
mentioning
confidence: 99%